Effect of Renal Denervation for the Management of Heart Rate in Patients With Hypertension: A Systematic Review and Meta-Analysis - Li, Le; Xiong, Yulong; Hu, Zhao; Yao, Yan (Frontiers in Cardiovascular Medicine, 2022)
Objective: The effect of renal denervation (RDN) on heart rate (HR) in patients with hypertension had been investigated in many studies, but the results were inconsistent. This meta-analysis was performed to evaluate the efficacy of RDN on HR control. Methods: Databases, such as PubMed, EMBASE, Cochrane, and ClinicalTrials.gov, were searched until September 2021. Randomized controlled trials (RCTs) or non-RCTs of RDN in hypertensive patients with outcome indicators, such as HR, were selected. Weighted mean difference (WMD) was calculated for evaluating the changes in HR from baseline using fixed-effects or random-effects models. The Spearman's correlation coefficients were used to identify the relationship between the changes of HR and systolic blood pressure (SBP). Results: In the current meta-analysis, 681 subjects from 16 individual studies were included. This study showed that RDN could reduce office HR in patients with hypertension [WMD = −1.93 (95% CI: −3.00 to −0.85, p < 0.001)]. In addition, 24-h HR and daytime HR were decreased after RDN [WMD = −1.73 (95% CI: −3.51 to −0.31, p = 0.017) and −2.67 (95% CI: −5.02 to −0.32, p = 0.026) respectively], but nighttime HR was not significantly influenced by RDN (WMD = −2.08, 95% CI: −4.57 to 0.42, p = 0.103). We found that the reduction of HR was highly related to the decrease of SBP (r = 0.658, p < 0.05). Conclusion: Renal denervation could reduce office, 24-h, and daytime HR, but does not affect nighttime HR. And the effect is highly associated with blood pressure (BP) control. Systematic Review Registration: https://www.crd.york.ac.uk/PROSPERO, identifier: CRD42021283065.